HUBUNGAN SPIRITUAL WELL-BEING DENGAN RESILIENSI KELUARGA PASIEN YANG DIRAWAT DI RUANG INTENSIVE CARE UNIT (ICU) - Tasya Putri Herisyhalina (2023)
Resilience is a process that involves the role of each individual which shows individual strength and toughness to rise from negative experiences and adversity when facing difficult situations and containing quite heavy obstacles. One factor that is assumed to be related to resilience is Spiritual Well-Being. Spiritual Well-Being is an expression of one's spiritual health, which is built from religious well-being and existential process well-being in individuals and can be used as an indicator of quality of life on spiritual dimensions and indicators. Objective: This study aims to determine the relationship between Spiritual Well-Being and family resilience of patients treated in the Intensive Care Unit (ICU). Method: The research method uses Cross Sectional with sampling techniques using purposive sampling with the number of samples 30 family in ICU. Results: The results of the Fisher Exact alternative analysis showed a p value of 0.014 < 0.05 so it can be concluded that there is a significant relationship between Spiritual Well-Being and the resilience of the families of patients treated in the ICU.